Penggunaan Instrumen Cello Dalam Langgam Jawa - Sudarno Sudarno (SELONDING, 2017)
Keroncong music is the result of a mixture of Portuguese culture and Indonesian culture around the year 1498. Java Javanese style which is one part of keroncong music develops well in Java as a form of community creativity. In 1934 was used pitchicato cello instrument that is picked the technique of strumming with fingers, by Tjok Shinsu. The cello instrument in its native country is a string instrument, by the Indonesians being transformed into a string instrument now known as "cello keroncong". Thanks to the creativity of the artists keroncong, then came the form of Langgam Jawa Keroncong, because according to Gesang that Langgam Jawa was born in 1950. While the Javanese Gamelan affects the original Keroncong, Macapat leads to the verses in Keroncong Langgam introduced by Gesang. The style of singing keroncong with Java elements is usually not displayed in the notation. The phenomenon is very interesting to explore further about the use of cello instruments in Langgam Keroncong. Research conducted with the object uses qualitative methods that rely on direct observation in the field in the pattern of cello instrument play. During the play Langgam Jawa the cello instrument plays a pattern of kendangan. The instrument gives an accentuation that gives the color of its own voice in a dish. The characteristic that stands out in Keroncong Javanese Langgam is located in the cello instrument game because in the form of the game imitate ciblon kendang. According to its function cello in Langgam Jawa Keroncong play a role as ritmis. The role of the cello instrument is the same as the kendang instrument that acts as a rhythm holder having the authority to carry the direction of the song to be performed, such as using ankle rhythm or double, or in karawitan called weled and rangkep.